Mutations in the Drosophila tricellular junction protein M6 synergize with Ras(V12) to induce apical cell delamination and invasion - Dunn, Brandon S. (Proc Natl Acad Sci U S A, 2018)
Complications from metastasis are responsible for the majority of cancer-related deaths. Despite the outsized medical impact of metastasis, remarkably little is known about one of the key early steps of metastasis: departure of a tumor cell from its originating tissue. It is well documented that cellular delamination in the basal direction can induce invasive behaviors, but it remains unknown if apical cell delamination can induce migration and invasion in a cancer context. To explore this feature of cancer progression, we performed a genetic screen in Drosophila and discovered that mutations in the protein M6 synergize with oncogenic Ras to drive invasion following apical delamination without crossing a basement membrane. Mechanistically, we observed that M6-deficient Ras(V12) clones delaminate as a result of alterations in a Canoe-RhoA-myosin II axis that is necessary for both the delamination and invasion phenotypes. To uncover the cellular roles of M6, we show that it localizes to tricellular junctions in epithelial tissues where it is necessary for the structural integrity of multicellular contacts. This work provides evidence that apical delamination can precede invasion and highlights the important role that tricellular junction integrity can play in this process.